Adult‐onset Still's disease initially thought to be an odontogenic infection: A case report. (7th May 2018) - Hino, Shunsuke; Nakamura, Satoshi; Kaneko, Takahiro; Horie, Norio; Shimoyama, Tetsuo
Abstract : Objective: To present a case of Adult‐onset Still's disease (AOSD) initially suspected to be odontogenic inflammation. Background: Adult‐onset Still's disease is a rare, complex autoinflammatory disease and a known cause of fever of unknown origin. Materials and methods: The patient had both a fever and dental pain. Following meticulous examination, the patient was diagnosed with AOSD. Conclusion: Clinicians should keep in mind that a patient such as AOSD may visit their clinics.